2017
DOI: 10.1038/tp.2017.138
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, prefrontal cortex hypomyelination and cognitive symptoms in schizophrenia

Abstract: Schizophrenia (SZ) is a neurodevelopmental disorder with a broad symptomatology, including cognitive symptoms that are thought to arise from the prefrontal cortex (PFC). The neurobiological aetiology of these symptoms remains elusive, yet both impaired redox control and PFC dysconnectivity have been recently implicated. PFC dysconnectivity has been linked to white matter, oligodendrocyte (OL) and myelin abnormalities in SZ patients. Myelin is produced by mature OLs, and OL precursor cells (OPCs) are exceptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 196 publications
(204 reference statements)
6
106
0
6
Order By: Relevance
“…Finally, there are also other concepts and hypotheses of SZ, including the cannabinoid hypothesis of SZ [44]. There are also reports about the role of inflammation [45,46] and oxidative stress [47] in this disease.…”
Section: Disturbances In Neurotransmission In Szmentioning
confidence: 99%
“…Finally, there are also other concepts and hypotheses of SZ, including the cannabinoid hypothesis of SZ [44]. There are also reports about the role of inflammation [45,46] and oxidative stress [47] in this disease.…”
Section: Disturbances In Neurotransmission In Szmentioning
confidence: 99%
“…There are studies that show that the production of ectopic aerobic ATP of myelin sheaths is related to the oxidative damage of the myelin sheaths, while the oxidative stress induced by ICH can be shown as demyelination. Demyelination reduces the use of lactic acid produced by the axonal myelin and leads to axonal damage due to axon‐glial metabolic coupling disorder (Table ) …”
Section: Pathophysiology Of Wmi After Ichmentioning
confidence: 99%
“…Demyelination reduces the use of lactic acid produced by the axonal myelin and leads to axonal damage due to axonglial metabolic coupling disorder (Table 1). 35,36…”
Section: Pathophys I Ology Of Wmi Af Ter Ichmentioning
confidence: 99%
“…Damage from OS on oligodendrocytes and neurons has been found to be associated with active demyelination and axonal or neuronal damage in MS . Studies have revealed that OS modulates OPC signal processes which are vital for OPC proliferation and differentiation resulting in hypomyelination …”
Section: Elucidation Of the Role Of Oxidative Stress (Os) And Mitochomentioning
confidence: 99%
“…47,48 Damage from OS on oligodendrocytes and neurons has been found to be associated with active demyelination and axonal or neuronal damage in MS. 42 Studies have revealed that OS modulates OPC signal processes which are vital for OPC proliferation and differentiation resulting in hypomyelination. 49,50 Moreover, research indicates that myelin sheath can conduct aerobic metabolism, generating ROS which can result in OS. 41 Isolated myelin has been shown to produce OS biomarkers as well as antioxidant defense biomarkers, suggesting that the axonal degeneration associated with myelin loss in demyelinating diseases is related to OS caused by impaired myelin oxidative phosphorylation.…”
Section: Neurodegeneration Demyelination and Axonal Loss In Msmentioning
confidence: 99%